The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.7717/peerj.2811
|View full text |Cite
|
Sign up to set email alerts
|

Floral development and vascularization help to explain merism evolution inPaepalanthus(Eriocaulaceae, Poales)

Abstract: BackgroundFlowers in Eriocaulaceae, a monocot family that is highly diversified in Brazil, are generally trimerous, but dimerous flowers occur in Paepalanthus and a few other genera. The floral merism in an evolutionary context, however, is unclear. Paepalanthus encompasses significant morphological variation leading to a still unresolved infrageneric classification. Ontogenetic comparative studies of infrageneric groups in Paepalanthus and in Eriocaulaceae are lacking, albeit necessary to establish evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Investigations of the vascular anatomy of flowers was introduced by van Tieghem (1871), and is still successfully applied in the investigation of monocots (Dyka, 2018;Novikoff & Kazemirska, 2012;Remizowa et al, 2010;Zalko & Deroin, 2018). Because of its evolutionary conservation, the floral vascular system can serve not only for direct comparison of different taxa, but also for the elucidation of fused organs and analysis of floral evolution and morphogenesis (Joshi, 1940;Novikoff & Jabbour, 2014;Nuraliev et al, 2021;Silva et al, 2016;Sokoloff et al, 2018). Similarly, the principles of the gynoecium vertical zonality were developed by Leinfellner (1950) and Baum (1952), but are still useful in solving phylogenetic and taxonomic issues, in combination with morphological and molecular data (Heigl et al, 2020;Odintsova et al, 2013;Oliveira et al, 2020;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the vascular anatomy of flowers was introduced by van Tieghem (1871), and is still successfully applied in the investigation of monocots (Dyka, 2018;Novikoff & Kazemirska, 2012;Remizowa et al, 2010;Zalko & Deroin, 2018). Because of its evolutionary conservation, the floral vascular system can serve not only for direct comparison of different taxa, but also for the elucidation of fused organs and analysis of floral evolution and morphogenesis (Joshi, 1940;Novikoff & Jabbour, 2014;Nuraliev et al, 2021;Silva et al, 2016;Sokoloff et al, 2018). Similarly, the principles of the gynoecium vertical zonality were developed by Leinfellner (1950) and Baum (1952), but are still useful in solving phylogenetic and taxonomic issues, in combination with morphological and molecular data (Heigl et al, 2020;Odintsova et al, 2013;Oliveira et al, 2020;Silva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Poales, common petal-stamen primordia are present in Xyris [11,20] and Eriocaulon ( [8,11,23] and this study). The occurrence of common petal-stamen primordia in other genera of Eriocaulaceae, e.g., Paepalanthus, is controversial [11,28]. Remarkably, in most other monocots possessing common primordia, these occur only for inner whorl perianth members and corresponding stamens, even when the two perianth whorls are similar to each other in anthetic flowers (e.g.,Veratrum, Liliales, [2]; Dioscorea, Dioscoreales, [64]) or rarely for all perianth members and stamens on their radii.…”
Section: Discussionmentioning
confidence: 99%
“…The unusual nature of orientation of trimerous pentacyclic flowers in Eriocaulaceae highlights a need of more detailed comparative and developmental studies with attention to variation of flower groundplan in the family. The most obvious aspects of floral diversity in Eriocaulaceae are the reduction of the outer whorl of the androecium (its rudiments can be often traced in male flowers) in Paepalanthoideae, occurrence of dimery rather than trimery in some taxa, patterns of corolla tube formation and petal to stamen fusion [ 9 , 11 , 13 , 25 , 26 , 27 , 28 ]. In the present study, we explore the reported phenomenon of the absence of the inner perianth whorl (corolla) in female flowers of some species of Eriocaulon , e.g., [ 9 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such simultaneous initiation of numerous organs requires more space and meristematic material, leaving only a small area for gynoecium inception. Among Poales, common petal-stamen primordia have been reported for Xyridaceae (Remizowa et al, 2012;Nardi et al, 2021) and Eriocaulaceae (Stützel, 1984;Silva et al, 2016;Sokoloff et al, 2020). Simultaneous organ initiation but with separate primordia is also found in Rapateaceae.…”
Section: Floral Ontogenymentioning
confidence: 98%